Modeling the long-term antibody response of a hepatitis E vaccine. Issue 33 (7th August 2015) - Chen, Shu; Zhou, Zi; Wei, Fei-Xue; Huang, Shou-Jie; Tan, Zhong; Fang, Ya; Zhu, Feng-Cai; Wu, Ting; Zhang, Jun; Xia, Ning-Shao
Abstract : Highlights: This is the first report regarding the long-term antibody response modeling of HEV 239 vaccine. Two models used in this study were fit well using the anti-HEV IgG data from 1278 baseline seronegative vaccine recipients. The HEV 239 vaccine is predicted to provide from 8 years to near life-long persistence of anti-HEV IgG above detectable levels. Model predictions in this study are based on conservative mathematical assumptions. Abstract: Background: The first commercialized hepatitis E vaccine, HEV 239, has been shown to be safe and highly immunogenic, the protection as well as the vaccine-induced anti-HEV maintained for at least 4.5 years. However, the longer term persistence of the vaccine-induced anti-HEV responses is unknown. Methods: Two statistical models, the power-law model and the modified power-law model, were applied to predict the long-term antibody response of the HEV 239 vaccine. The models were fit using the anti-HEV IgG data from a modeling subpopulation of 1278 baseline seronegative vaccinees who seroconverted within one month after finishing the whole vaccination course in the phase 3 trial of HEV 239. In addition, antibody data from a validation subpopulation were used to validate the robustness of the derived models. Results: In the vaccinees without pre-vaccination immunity, the power-law model and the modified power-law model estimated that the median duration of the detectable antibody (≥0.077 WU/ml) was 8 years and 13 years, respectively. The power-law model and the modified power-law model estimated that 50% of these vaccinees will maintain detectable levels of anti-HEV IgG for 8 years and >30 years, respectively. Conclusions: The recombinant hepatitis E vaccine HEV 239 is predicted to provide from 8 years to nearly life-long persistence of anti-HEV IgG above detectable levels. Model predictions are based on conservative mathematical assumptions. (NCT01014845).